Evaluación de la presencia en Internet de los principales operadores logísticos en España - Miranda González, Francisco Javier; Chamorro Mera, Antonio; Rubio Lacoba, Sergio; Reveriego Mogollón, Laura (Cuadernos de Estudios Empresariales, 2006)
New technologies and, especially Internet, are changing the logistics provider management styles and their services offer. So, it would be very interesting to assess the main Spanish logistics provider web presence, analyzing the quality of their corporate web sites. Among the different web sites assessment methods developed in the last years, we have selected the Web Assessment Index (WAI), adapted to the special characteristics of this industry. This index, already used in other sectors, allows us to value content and operative issues of these web sites. The WAI final value is determinated by 22 factors grouped in 4 main components: content quality, accessibility, speed and navigability. Our results show the differences among companies: so, business with higher sales have web sites with higher WAI value.